Willingness to use a drug consumption room among people who use drugs in Lyon, France, a city with no open scene of drug use (the TRABOUL survey) - Mathieu Chappuy; Philippe Lack; Baptiste David; Gilles Penavayre; Damien Thabourey; Maira Landulpho; Anthony Plasse; Christophe Icard; François Bailly; Faroudja Boutahra; Pierre Pradat; Marianne Maynard; et al. (BMC, 2023)
Abstract Background Drug consumption rooms (DCRs) have been developed in cities with open drug scenes, with the aim to reduce drug-related harm. In Lyon, France's second-largest city, there is no distinct drug use area, which raised doubts regarding the need for a DCR. Methods We conducted a face-to-face survey of 264 people who use drugs (PWUDs), recruited in harm reduction or addiction treatment centers, in the streets or in squats. We assess their willingness to use a DCR, and we collected sociodemographic and medical features. Bivariable comparisons and analyses adjusted for sociodemographic parameters explored the association between willing to use a DCR and other variables, thus providing crude (ORs) and adjusted odds ratios (aORs) and 95% confidence intervals (95% CI). Results In total, 193 (73.1%) PWUDs accepted to participate (mean age 38.5 ± 9.3 years; 80.3% men). Among them, 64.2% declared willing to use a DCR. Being treatment-seeker (aOR 0.20, 95% CI [0.08-0.51]; p < 0.001) and not living alone (aOR 0.29; 95% CI [0.10-0.86], p = 0.025) were negatively associated with willing to use a DCR. By contrast, receiving precarity social insurance (aOR 4.12; 95% CI [1.86-9.14], p < 0.001), being seropositive for hepatitis C (aOR 3.60; 95% CI [1.20-10.84], p = 0.022), being cannabis user (aOR 2.45; 95% CI [1.01-5.99], p = 0.049), and reporting previous problems with residents (aOR 5.99; 95% CI [2.16-16.58], p < 0.001) or with the police (aOR = 4.85; 95% CI [1.43-16.39], p = 0.011) were positively associated. Conclusions PWUDs, especially the most precarious ones, largely supported the opening of a DCR in Lyon, a city with no open drug scene.